Leaf:Fruit Ratio and Vine Water Status Effects on Grenache Noir (Vitis vinifera L.) Berry Composition: Water, Sugar, Organic Acids and Cations - Etchebarne, F.; Ojeda, H.; Hunter, J.J. (South African Journal of Enology and Viticulture, 2016)
Seasonal variation in the water, sugar, organic acid and cation contents of developing grape berries (Vitis vinifera L. ‘Grenache noir’) under different levels of water supply (with and without deficit irrigation) and leaf:fruit ratios (18, 10 and five leaves per primary shoot, with one bunch per shoot), were investigated over two successive years in Mediterranean conditions (South of France). Fourteen shoots per vine were left for each leaf:fruit ratio level, and each vine was considered as having homogeneous primary shoots. The growth rate of the berries was increased with irrigation. Total dry matter content of the berry was not affected by leaf:fruit ratios, but the sugar loading decreased during berry development with a lower leaf:fruit ratio (five leaves per bunch). Treatments had little effect on organic acid contents and pH. Berry cation accumulation depended on vine water status and not on the total leaf area of the vine. Under irrigated conditions, calcium continued to accumulate in the berries after véraison. This confirms a partial functioning of the berry xylem during the post-véraison period. The seasonal variation in berry composition was less dependent on the leaf:fruit ratio than on the water status of the vine (mainly cations and sugar). This study provides evidence for the importance of plant water status effects on berry composition, irrespective of the leaf:fruit ratio. Vine water status is a major regulating factor for source-sink relationships.